FOREIGN EXPERIENCES IN REGULATING CAPITAL MARKET ACTIVITIES - Sardor Ulmasovich (Innovation Science and Technology, 2025)
This article examines the perspectives of various scholars on capital market regulation, focusing on foreign experiences in this field. It analyzes different regulatory models, listing requirements, and the characteristics of companies listed on international stock exchanges. Based on the analysis, relevant conclusions are drawn.